Prevalence of Anemia Among Tuberculosis Patients in Nepal: An Observational Cross-Sectional Study - Kc, Surya; Paudel, Amrita (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Anemia is a common co-morbidity among people with TB and is associated with a poor prognosis. Tuberculosis is one of the deadliest diseases and a major burden on the healthcare system in Nepal. The prevalence of anemia in tuberculosis is high, which range from 20% to 64%. The objective of the study is to determine the prevalence of anemia among tuberculosis patients in Nepal, focusing on its severity (mild and moderate) and morphological types (microcytic, normocytic, and macrocytic). Method: A retrospective cross-sectional study was conducted among the new case of pulmonary tuberculosis patients who were diagnosed at OPD over four years period. Data was collected from the hospital record system after obtaining ethical approval from the Institutional Review Committee. Previous cases of tuberculosis, HIV co-infected, hematological, and kidney patients were excluded. Serum hemoglobin, demographic variables, and red blood cell parameters were obtained from the Hospital Record System. Anemia was defined based on WHO guidelines, and its severity was categorized as mild, moderate, or severe. Morphological classification was done using RBC indices. Convenience sampling was used. Point estimate and 95% confidence interval were calculated. Results: Among 320 tuberculosis patients, the prevalence of anemia was 235 (73.75%) (95% confidence interval: 68.60–78.25). Most patients with anemia (78.7%) had mild anemia, followed by 16% with moderate anemia and 5% with severe anemia. Normocytic normochromic anemia was the most common morphological pattern (51.25%), followed by microcytic anemia (36%) and macrocytic anemia (10%). Anemia was more prevalent in females (63.8%) compared to males (36.2%) and was higher in older adults, with 69% of anemic patients aged 65 years or older. A majority of patients with anemia (73%) were from lower socioeconomic backgrounds, and 65.1% were malnourished with a BMI below 18.5 kg/m². Conclusion: The occurrence of anemia among tuberculosis patients in Nepal was found to be high, consistent with findings from numerous studies worldwide